Develop and Apply Electrocardiography-Based Risk Score to Identify Community-Based Elderly Individuals at High-Risk of Mortality - Lu, Tzu-Pin; Chattopadhyay, Amrita; Lu, Kuan-Chen; Chuang, Jing-Yuan; Yeh, Shih-Fan Sherri; Chang, I-Shou; Chen, Ching-Yu Julius; Wu, I-Chien; Hsu, Chih-Cheng; Chen, Tzu-Yu; Tseng, Wei-Ting; Hsiung, Chao Agnes; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: With an aging world population, risk stratification of community-based, elderly population is required for primary prevention. This study proposes a combined risk-score developed using electrocardiographic (ECG) parameters and determines its long-term prognostic value for predicting cardiovascular mortality. Methods and Results: A cohort-study, conducted from December 2008 - April 2019, enrolled 5,380 subjects in Taiwan, who were examined, using three-serial-12-lead ECGs, and their health/demographic information were recorded. To understand the predictive effects of ECG parameters on overall-survival, Cox hazard regression analysis were performed. The mean age at enrollment was 69.1±8.2 years, and 47.8% were males. ECG abnormalities, LVH (hazard ratio (HR) = 1.43, 95% confidence intervals (CI) = (1.11–1.85), P = 0.005) and PR interval (HR = 2.06, CI = (1.32–3.23), P = 0.002), were significantly associated with primary outcome all-cause deaths. Furthermore, LVH (HR = 1.97, CI = (1.05–3.74), P = 0.036) was significantly associated with outcome, cardiovascular death, while PR interval (HR = 6.74, CI = (2.68–16.92), P = 0.00005) was a significant predictor for outcome, unexplained death. Overall, the ECG risk score could successfully classify samples into (high and low) risk groups, and could predict people, susceptible to all three death outcomes (P < 0.05). Statistically significant (P<0.001) improvement of the C-indices further demonstrated the robustness of the prediction model with ECG parameters. Conclusions: The ECG-based risk score is highly associated with increased risk of mortality in elderly population and may be successfully used in clinical practice.